Studies on Xanthine Oxidase - Malcolm Dixon (1925)
Research Article| January 01 1925 Studies on Xanthine Oxidase: The Function of Catalase Malcolm Dixon Malcolm Dixon 1The Biochemical Laboratory, Cambridge Search for other works by this author on: This Site PubMed Google Scholar Biochem J (1925) 19 (3): 507–512. https://doi.org/10.1042/bj0190507 Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Share Icon Share MailTo Twitter LinkedIn Cite Icon Cite Get Permissions Citation Malcolm Dixon; Studies on Xanthine Oxidase: The Function of Catalase. Biochem J 1 January 1925; 19 (3): 507–512. doi: https://doi.org/10.1042/bj0190507 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsBiochemical Journal Search Advanced Search This content is only available as a PDF. © 1925 CAMBRIDGE UNIVERSITY PRESS1925 Article PDF first page preview Close Modal You do not currently have access to this content.